Influence of colemanite admixture on Portland cement durability - Erdogmus, Ertugrul; Targan, Serif; Erdogan, Yunus; Avciata, Ulvi; Gencel, Osman (ICE PUBLISHING, 2012)
In this study, the compressive strength of mortar prepared by Portland cement (PC) and different proportions of blast furnace slag, fly ash and colemanite concentrator waste was examined at the end of the 2nd, 7th, 28th, 60th and 90th days. Moreover, some mortars were kept in 50 g/l sodium sulfate (Na2SO4) solution according to ASTM C1012 for 6 months to determine their sulfate resistance. The first length of some mortars made with alkali reactive sand together with additives mentioned above or PC according to ASTM C1260 was measured to detect their alkali-aggregate reaction resistance and then their final lengths were measured after being kept in 1 M sodium hydroxide (NaOH) solution at a temperature of 80 degrees C for 14 days. The results were compared both among themselves and with Portland cement. In addition, the microstructures of some samples scanned by scanning electron microscopy were photographed. It was found that all the additives had positive effects on sulfate and ASR resistance.
Keywords: FLY-ASH; SULFATE ATTACK; BLENDED CEMENTS; BOTTOM ASH; NATURAL POZZOLANS; SILICA FUME; ORE WASTE; CONCRETE; RESISTANCE; PERFORMANCE; Construction & Building Technology; Materials Science